Dietary Antioxidants and lipid Profile of smokers - Prethi N R (Department of Home Science, College of Agriculture, 2002)
The study entitled 'Dietary antioxidants and lipid profile of smokers' comprises information on the influence of various socio-economic and dietary profiles, as well as smoking habits on the health profile of selected respondents. The study was conducted among 100 adult males, who used more than 10 cigarettes a day and were in the habit of smoking for at least the past 10 • years. Analysis of the smoking habit of respondents revealed that more than 50 per cent of the respondents were in the habit of smoking 10 to 15 cigarettes a day, while 14 per cent smoked more than 30 cigarettes a day. More number of them had been smoking for the past 10 to 15 years. The socio-economic profile of the smokers indicated that most of the respondents were in the age group of 36 to 40 years. Majority of the respondents were having an educational status of high school level. The occupational distribution of the respondents were more or less the same. Most of the respondents were married and were residing in nuclear families with four members. Majority of the respondents surveyed were having a monthly income between Rs. 2501 to 5000 On assessing the frequency of use of antioxidant rich food items. most of them used foods like milk and fats and oi Is most frequently while the least popular foods were flesh foods.